Comparison of the `11+ Kids` injury prevention programme and a regular warmup in children`s football (soccer): a cost effectiveness analysis - Rössler, R.; Verhagen, E.; Rommers, N.; Dvorak, J.; Junge, A.; Lichtenstein, E.; Donath, L.; Faude, O. (British Journal of Sports Medicine, 2019)
Objective: To evaluate a potential reduction in injury related healthcare costs when using the `11+ Kids` injury prevention programme compared with a usual warmup in children`s football.